Stereotactic body radiotherapy for pancreatic cancer: recent progress and future directions. Issue 5 (3rd May 2016) - Myrehaug, Sten; Sahgal, Arjun; Russo, Suzanne M.; Lo, Simon S.; Rosati, Lauren M.; Mayr, Nina A.; Lock, Michael; Small, William; Dorth, Jennifer A.; Ellis, Rodney J.; Teh, Bin S.; Herman, Joseph M.
ABSTRACT: Despite advances in surgical, medical, and radiation therapy for pancreatic cancer, the prognosis remains poor. At this time, the only chance for long-term survival is surgical resection. More challenging is the optimal management of unresectable locally advanced pancreatic cancer, which has historically been treated with concurrent chemoradiation or chemotherapy alone. However, the survival and local control benefit of conventional radiotherapy in addition to chemotherapy was unclear. More recently, stereotactic body radiotherapy (SBRT) is emerging as a viable approach to maximizing local tumor control with a tolerable side effect profile. SBRT achieves sharp dose fall-off facilitating safe delivery of highly focused radiation to the tumor over 1-5 days. Although the optimal regimen of pancreas SBRT has not yet been established, its short treatment course limits the delay of additional. Future directions involve prospective study of pancreas SBRT and exploration of biomarkers and imaging technology in order to adopt a personalized management paradigm.